Strategi Optimalisasi Penghimpunan Zakat Profesi Di Badan Amil Zakat Nasional (BAZNAS) Kabupaten Mandailing Natal: Nur Indah Hidayah - Nur Indah Hidayah (Program Studi Perbankan Syariah Jurusan Syariah, Ekonomi dan Bisnis Islam Sekolah Tinggi Agama Islam Negeri Mandailing Natal (STAIN MADINA), 2026)
This study aims to examine the strategies for optimizing the collection of professional zakat within the National Amil Zakat Agency (BAZNAS) of Mandailing Natal Regency.This research is a qualitative descriptive study that seeks to describe and explain the strategies employed by BAZNAS Mandailing Natal in collecting professional zakat. The study not only presents the facts but also analyzes the supporting factors and obstacles encountered in the process of optimizing the collection of professional zakat in Mandailing Natal. Regency Research Findings The optimization strategy demonstrates the collection of professional zakat in Mandailing Natal Regency, namely by socializing the data collection of mustahit in all sub-districts, collaborating with the local government, and aligning with regional regulations. Professional Optimization Strategy BAZNAS Mandailing Natal faces several challenges, as the establishment of UPZ (Unit Pengumpul Zakat/ Zakat Collecting Units) is still under evaluation. The potential of professional zakat in BAZNAS Mandailing Natal is not yet fully realized because the community is accustomed to giving zakat directly to relatives or close individuals rather than through BAZNAS. Additionally, some civil servants (PNS) still lack sufficient knowledge about professional zakat. The solutions implemented by BAZNAS Mandailing Natal to optimize professional zakat include maximizing the collection of zakat from various sources, such as wealthy individuals and companies operating within Mandailing Natal Regency. Keywords: Optimization, Collection, Zakat, BAZNAS